Factors Affecting Beef Demand in Kendari City Southeast Sulawesi (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2022)
The research aims to determine the factors that influence the demand for beef in the city of Kendari. The data used is secondary data (time series) for 5 years in the form of beef demand data (kg), beef price (Rp/kg), population (person), people's per capita income (Rp), chicken meat price (Rp /kg) and the price of rice (Rp/kg). Data were analyzed using multiple linear regression analysis. The results of the study show that the factors that influence the demand for beef in Kendari City are the price of beef, population, income, rice prices and chicken prices. Beef prices, population, people's income, and chicken prices have a significant effect on the demand for beef in Kendari City.